Ultrasound in first trimester - Zubairi, Tanveer Khalid (Paramount, 2013)
This is basic reference book to help Sonologist, Obstetrician and Gynaecologist. It provides the basic conceptual, factual and interpretive material required for clinical practice. Divided into several parts, it helps in recognition of the normal anatomy and differential diagnosis of different pathologies.